Biotin pathway in novel Fodinibius salsisoli sp. nov., isolated from hypersaline soils and reclassification of the genus Aliifodinibius as Fodinibius - Galisteo, Cristina; de la Haba, Rafael R.; Sánchez-Porro, Cristina; Ventosa, Antonio (Frontiers in Microbiology, 2023)
Hypersaline soils are extreme environments that have received little attention until the last few years. Their halophilic prokaryotic population seems to be more diverse than those of well-known aquatic systems. Among those inhabitants, representatives of the family Balneolaceae (phylum Balneolota) have been described to be abundant, but very few members have been isolated and characterized to date. This family comprises the genera Aliifodinibius and Fodinibius along with four others. A novel strain, designated 1BSP15-2V2T, has been isolated from hypersaline soils located in the Odiel Saltmarshes Natural Area (Southwest Spain), which appears to represent a new species related to the genus Aliifodinibius. However, comparative genomic analyses of members of the family Balneolaceae have revealed that the genera Aliifodinibius and Fodinibius belong to a single genus, hence we propose the reclassification of the species of the genus Aliifodinibius into the genus Fodinibius, which was first described. The novel strain is thus described as Fodinibius salsisoli sp. nov., with 1BSP15-2V2T (= CCM 9117T = CECT 30246T) as the designated type strain. This species and other closely related ones show abundant genomic recruitment within 80 - 90 % identity range when searched against several hypersaline soil metagenomic databases investigated. This might suggest that there are still uncultured, yet abundant closely related representatives to this family present in these environments. In-depth in-silico analysis of the metabolism of Fodinibius showed that the biotin biosynthesis pathway was present in the genomes of strain 1BSP15-2V2T and other species of the family Balneolaceae, which could entail major implications in their community role providing this vitamin to other organisms that depend on an exogenous source of this nutrient.